Phosphorus and zinc uptake and their interaction effect on dry matter and chlorophyll content of sweet corn (Zea mays var. Saccharata) - Soltangheisi, Amin; Ishak, Che Fauziah; Musa, Mohamed Hanafi; Zakikhani, Hamed; Abdul Rahman, Zaharah (Asian Network for Scientific Information, 2013)
Zinc and Phosphorus have antagonistic effect on the absorption and translocation of each other in plants. P-induced Zn deficiency is more common than Zn-induced P deficiency because growers commonly apply large amounts of P fertilizer as compared to Zn fertilizer. This research was conducted to examine the effect of different levels of Zn and P on the yield, Zn and P uptake and chlorophyll contents of corn plants. Sweet corn was grown in nutrient culture containing all combinations of Zn as ZnSO4.7H2O at levels of 0.0, 5.0, 10.0 and 20.0 mg L-1 and of P as KH2PO4 at levels of 0.0, 20.0, 40.0 and 80.0 mg L-1. Zn0P20 treatment produced the highest yield and the yields were decreased with P application in combination with Zn. The lowest dry weight of young corn plants was recorded under Zn0P80 treatment at both harvesting times due to both Zn deficiency and P toxicity. Chlorophyll content decreased with high Zn and P applications and this can be attributed to the interactions of Zn and P with iron in the growth medium. Zn0P80 treatment had the lowest Zn and the highest P uptake by shoot at 14 days after transplanting. The study has shown that Zn deficiency can enhance P uptake and translocation to such an extent that P may accumulate to toxic level in leaves. Zn20P80 treatment produced the highest Zn and P uptake by roots. Zn and P uptake by roots increased with increased Zn and P supply.